2015
DOI: 10.1017/s1368980015001469
|View full text |Cite
|
Sign up to set email alerts
|

Buying health: assessing the impact of a consumer-side vegetable subsidy on purchasing, consumption and waste

Abstract: Objective: To measure the impact of a reimbursement-based consumer subsidy on vegetable expenditures, consumption and waste. Design: Two-arm randomized controlled trial; two-week baseline observation period, three-week intervention period. Participants' vegetable expenditures, consumption and waste were monitored using receipts collection and through an FFQ. During the intervention period, the treatment group received reimbursement of up to 50 US dollars ($) for purchased vegetables. Setting: Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The effect of in-kind incentives on children was investigated by two studies reporting toy premiums significantly increased children’ purchases (tracked by scan cards) of healthier and low-calorie meals in fast-food restaurants, and FV snacks in local zoos( Hobin et al, 2012 ; Karpyn et al, 2017 ). Fifteen studies focused on the effect of financial incentives on dietary intake ( Jilcott Pitts et al, 2018a ; Geliebter et al, 2013 ; Waterlander et al, 2013a ; Harnack et al, 2016 ; Ball et al, 2015 ; Kral et al, 2016 ; Bernales-Korins et al, 2017 ; Smith-Drelich, 2016 ; Franckle et al, 2018 ), purchases ( Waterlander et al, 2013a , 2013b ; Ball et al, 2015 ; Kral et al, 2016 ; Bernales-Korins et al, 2017 ; Smith-Drelich, 2016 ; Franckle et al, 2018 ; Blakely et al, 2011 ; Guan et al, 2018 ; Banerjee and Nayak, 2018 ; Polacsek et al, 2018 ; Gopalan et al, 2019 ), and BMI ( Jilcott Pitts et al, 2018a ; Geliebter et al, 2013 ; Waterlander et al, 2013a ; Harnack et al, 2016 ; Kral et al, 2016 ), among adult samples. The type of financial incentives varied, including different levels of price reductions ( Jilcott Pitts et al, 2018a ; Geliebter et al, 2013 ; Waterlander et al, 2013a , 2013b ; Harnack et al, 2016 ; Ball et al, 2015 ; Bernales-Korins et al, 2017 ; Blakely et al, 2011 ; Polacsek et al, 2018 ), coupons for targeted products ( Franckle et al, 2018 ; Guan et al, 2018 ; Banerjee and Nayak, 2018 ), and cash back payments (reimbursements) ( Kral et al, 2016 ; Smith-Drelich, 2016 ; Gopalan et al, 2019 ) based on purchasing behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of in-kind incentives on children was investigated by two studies reporting toy premiums significantly increased children’ purchases (tracked by scan cards) of healthier and low-calorie meals in fast-food restaurants, and FV snacks in local zoos( Hobin et al, 2012 ; Karpyn et al, 2017 ). Fifteen studies focused on the effect of financial incentives on dietary intake ( Jilcott Pitts et al, 2018a ; Geliebter et al, 2013 ; Waterlander et al, 2013a ; Harnack et al, 2016 ; Ball et al, 2015 ; Kral et al, 2016 ; Bernales-Korins et al, 2017 ; Smith-Drelich, 2016 ; Franckle et al, 2018 ), purchases ( Waterlander et al, 2013a , 2013b ; Ball et al, 2015 ; Kral et al, 2016 ; Bernales-Korins et al, 2017 ; Smith-Drelich, 2016 ; Franckle et al, 2018 ; Blakely et al, 2011 ; Guan et al, 2018 ; Banerjee and Nayak, 2018 ; Polacsek et al, 2018 ; Gopalan et al, 2019 ), and BMI ( Jilcott Pitts et al, 2018a ; Geliebter et al, 2013 ; Waterlander et al, 2013a ; Harnack et al, 2016 ; Kral et al, 2016 ), among adult samples. The type of financial incentives varied, including different levels of price reductions ( Jilcott Pitts et al, 2018a ; Geliebter et al, 2013 ; Waterlander et al, 2013a , 2013b ; Harnack et al, 2016 ; Ball et al, 2015 ; Bernales-Korins et al, 2017 ; Blakely et al, 2011 ; Polacsek et al, 2018 ), coupons for targeted products ( Franckle et al, 2018 ; Guan et al, 2018 ; Banerjee and Nayak, 2018 ), and cash back payments (reimbursements) ( Kral et al, 2016 ; Smith-Drelich, 2016 ; Gopalan et al, 2019 ) based on purchasing behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed results were found for the impact of cash back payments on healthy food purchases (measured by checking receipts) as one study incentivizing vegetable purchases in supermarkets found positive results ( Smith-Drelich, 2016 ), while two studies that incentivized a variety of healthy items reported null ( Kral et al, 2016 ; Gopalan et al, 2019 ). These studies are RCTs with low risk of bias score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While past research has explored strategies such as serving more of a vegetable [39], serving a wider variety of vegetables [40] and offering a vegetable subsidy (price reduction) to make them more affordable [41] to increase vegetable intake, focus group findings here suggest that tasting or sampling opportunities as well as preparation suggestions and demonstrations may be effective means to introduce consumers to new vegetables. Additional research is needed to better explain the interaction of favorite vegetables and frequently eaten vegetables.…”
Section: Discussionmentioning
confidence: 79%
“…Sixty-six studies looked at the impact of interventions on store sales and ROI for the food retailer. Fifty studies reported an increase in store sales after the intervention, with the greatest outcomes produced by coupon/vouchers (n ¼ 11), 68-71,89,98,103,106,107,109,124 signage, displays and nutrition labels (n ¼ 8), 149,151,153,158,159,164,165,167 rebate programs (n ¼ 4), 88,90,93,130 and a combination of incentive programs with pathto-purchase marketing (n ¼ 3). 182,199,200 Nutritional Quality of Shopping Purchases.…”
Section: Intervention Effectivenessmentioning
confidence: 99%